Peranan Cloud Computing Dalam Bisnis Perusahaan - Hans Christian Marwi (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2021)
Cloud computing has existed almost at the same time as when the Internet was introduced to the public. But this term is not as popular as the Internet in many countries, for example in Indonesia. Although cloud computing has been widely used for storages and backups, there are more of its capabilities that have not been explored. This paper aims to introduce the advantages of cloud computing for business, since many small and medium enterprises can not afford to develop their own websites at their local premises. The main reasons for that condition are inadequate fund for the costs and the lack of IT staff to develop and maintain their websites. With cloud computing, those enterprises can compete on the virtual world with small costs.